Regional variation in health is predominantly driven by lifestyle rather than genetics - Carmen Amador (Nature Portfolio, 2017)
Health-related traits are known to vary geographically. Here, Amador and colleagues show that regional variation of obesity-related traits in a Scottish population is influenced more by lifestyle differences than it is by genetic differences.